Red Scare Three - Granite Adams Unger (The Journal of Intelligence, Conflict and Warfare, 2021)
This article documents the history of united front work in Canada. It demonstrates how the Chinese Communist Party has long been engaged in a persistent campaign of interference in our politics and how the Canadian political establishment has been slow in recognizing this fact. It also seeks to explain why this realization was so slow in coming. Finally, it concludes by offering two alternative visions for how Canada might address this threat now that it has been recognized and makes a brief case for which is preferable.